Worshipping creation or the creators? / Rafidah Abas - Abas, Rafidah (Faculty of Hotel & Tourism Management, UiTM Pulau Pinang, 2019)
The Quran acknowledges four sacred months namely, Muharram, Rajab, Dzul Qaedah and Zulhijjah. Despite not listed, Ramadhan is the most blessed month in Islam. Indeed, of the 12 lunar months in Islam, some Muslims only knows Ramadhan which marked the fasting season and Syawal (the Eid). The greatness of Ramadhan is testified by the Almighty in two auspicious occasions of Quranic revelation. Ibn Kathir narrated that Lailatul Qadr (the night of Decree), is the night where the complete Quran is descended from al-Lawh al Mahfuz (the Preserved Tablet/Slate) to Baitul Izzah (the House of Might). It is then revealed to the prophet ig by the archangel Gabriel in the 17th of Ramadhan for twenty-three years in few stages. Unlike Nuzul Quran, Lailatul Qadr has no specific date. The most sacred night, which is greater than a thousand month (Quran: 97:3) is observed in any of the odd day of the last ten days of Ramadhan. In Malaysia, the eagerness to welcome Ramadhan starts when people post forgiveness messages or asking others to simply forgive their misconduct. Some even think that they are forgiven once they started to post the messages in social media, smile or talk again to the person despite being informed that Islam outlines several requirements that one must fulfil to seek forgiveness with other humans. The ultimate aims include preservation of life, to show remorse and to safeguard every Muslim’s rights.